Dialog Peradaban dalam Pendidikan: Peran Penerapan Terjemahan Karya Ulama Islam pada Masa Renaissance (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to analyze the role of applying translations of the works of Muslim scholars during the Renaissance as an important historical component in education. The research employs a qualitative approach using a library research design. Data collection is conducted through a systematic review of relevant literature. The data sources include academic books, reputable scholarly journals, policy documents, research reports, and other relevant literature. Data analysis is carried out through categorization, interpretation, and thematic synthesis of the literature findings in order to draw systematic conceptual conclusions. To ensure data validity, this study applies source triangulation by comparing various references from different academic backgrounds. The results and discussion indicate that Islamic civilization played a significant role in the emergence of the Western Renaissance and the advancement of modern science. Scientific development occurred through cross-civilizational exchanges rather than in isolation. During the Islamic Golden Age, Muslim scholars developed intellectual traditions that integrated revelation, reason, and empiricism. The works of Ibn Sina, Ibn Rushd, Al-Farabi, Al-Kindi, Al-Khawarizmi, and Ibn al-Haytham served as crucial bridges between Greek heritage and Europe’s intellectual revival. Through centers of learning in Baghdad, Andalusia, Cairo, and Damascus, Europe gained philosophy, medicine, mathematics, and scientific methods. The decline of Islamic science resulted from the collapse of political structures and scholarly institutions.